2019
DOI: 10.1007/s12237-019-00630-1
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of Nekton Recovery Following Marsh Restoration in the Northern Gulf of Mexico

Abstract: To investigate regional patterns in marsh recovery following restoration, a meta-analysis of nekton densities at restored and reference marshes in the northern Gulf of Mexico (GOM) was conducted. Results were variable at both restored and reference sites, but general trends with respect to the age of the restored site were observed. Pooled together, mean total nekton density in restored marshes during the first 5 years following restoration was approximately 50% of reference marsh densities [95% confidence int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 67 publications
(137 reference statements)
3
9
0
Order By: Relevance
“…We included data from both reference and restored sites in the northern GOM in our analysis. We acknowledge that species densities and composition may vary between restored and reference sites for a given habitat; many studies have documented differences between restored and natural marsh habitats in the GOM (e.g., Minello and Zimmerman 1992;Minello and Webb 1997;Rozas and Minello 2001;Zeug et al 2007;Hollweg et al 2019). This artifact of combining data from these two sources likely increases the variance in our estimates and may bias the results depending on the specific taxa.…”
Section: Meta-analysis To Estimate Mean Density By Species Habitat mentioning
confidence: 98%
“…We included data from both reference and restored sites in the northern GOM in our analysis. We acknowledge that species densities and composition may vary between restored and reference sites for a given habitat; many studies have documented differences between restored and natural marsh habitats in the GOM (e.g., Minello and Zimmerman 1992;Minello and Webb 1997;Rozas and Minello 2001;Zeug et al 2007;Hollweg et al 2019). This artifact of combining data from these two sources likely increases the variance in our estimates and may bias the results depending on the specific taxa.…”
Section: Meta-analysis To Estimate Mean Density By Species Habitat mentioning
confidence: 98%
“…Grabowski et al (2005) found that many species recruited to restored oyster reefs within weeks to months after restoration occurred, though complete reassembly is likely a much longer process. Studies comparing salt marsh restoration efforts to natural habitat have demonstrated that recovery is often slower (McSkimming et al 2016;Baumann et al 2018;Hollweg et al 2020b).…”
Section: Data Collection and Handlingmentioning
confidence: 99%
“…Marsh components often respond differentially to restoration, with some elements recovering faster than others. While aboveground biomass and vegetation cover may attain parity with reference conditions within a few years following restoration (Armitage et al 2014;Broome et al 2002;Ebbets et al 2019;Edwards and Proffitt 2003;LaSalle et al 1991), other components of the marsh may recover more slowly (Minello and Zimmerman 1992;Craft et al 1999;Craft et al 2002;Craft et al 2003;Ebbets et al 2019;Hollweg et al 2019) or never return to reference conditions within the project life or monitoring timeframe (Baumann et al 2018;Moreno-Mateos et al 2012;Zeug et al 2007). These varying recovery patterns, which have a strong effect on calculated net benefits, highlight the importance of considering multiple marsh components in the recovery of a restored marsh (Hollweg et al 2019;Strange et al 2002), including components such as belowground biomass, soil biogeochemical processes, and macroinvertebrate populations that tend to be slower to recover (Baumann et al 2018;Craft et al 2003;Ebbets et al 2019;Moreno-Mateos et al 2012;Zeug et al 2007).…”
Section: Potential Model Usesmentioning
confidence: 99%
“…Future efforts to refine this model should focus on the inputs that have the highest uncertainty or that have the most influence on model results. The limited data informing the recovery trajectories used for this model, combined with wide natural variability, highlight the need for additional, longer-term monitoring data at restored marsh sites (Baumann et al 2018;Ebbets et al 2019;Hollweg et al 2019). Monitoring of vegetation and fauna metrics at mature sites (e.g., > 5-10 years old) would improve understanding of the performance of older sites without requiring long-term studies.…”
Section: Recommended Future Researchmentioning
confidence: 99%